The Sexual Habits of Caracalla: Rumour, Gossip, and Historiography - Davenport, Caillan (Histos, 2017)
This paper examines two divergent traditions in Roman historiography about the sexual relationships of the emperor Caracalla. The first is that he had an affair with his mother, Julia Domna; the second is that he became impotent and indulged his desires with men. This article locates these two traditions in contemporary rumour and gossip about Caracalla, a young emperor who remained unmarried and childless throughout his sole reign. It ascribes their subsequent development and embellishment in historical and biographical accounts of Caracalla’s reign to popular conceptions of tyrannical young emperors, and in the case of Cassius Dio, to his aim of subverting Caracalla’s own public image.